Video games as a recovery intervention for ostracism. (August 2019) - Tamplin-Wilson, Jay; Smith, Rebecca; Morgan, Jessica; Maras, Pam
Abstract: Research has begun to explore the potential benefits of video games as intervention methods for a variety of issues. This study explores the role of video games in assisting the recovery from ostracism. Undergraduate volunteers ( n  = 117) were either included or excluded during a game of cyberball, after which their relational needs (self-esteem and belonging), as well as positive and negative affect were assessed. They were then randomly allocated to a video game condition (self-esteem enhancing, pro-social, or control) and following 5 min of play, needs and affect were reassessed. Participants' anti/pro – social responses were also recorded after administering the video game intervention. Results showed that all game conditions were successful in restoring psychological needs and affect scores following ostracism. Additionally, the pro-social game was the most successful in increasing positive affect following ostracism. There were no differences in pro-social behaviour scores between groups, with participants demonstrating neutral to social behaviour scores. This study is the first of its kind to demonstrate that games have the potential to restore needs and affect following ostracism. Exploring such low-cost and easily accessible intervention methods is crucial, given that ostracism is a prevalent issue with serious negative effects on wellbeing. This study adds to the growing research demonstrating the therapeutic benefits of video games, suggesting it is a valuable method of intervention for ostracism that needs to be further explored. Highlights: Videogames successfully restored depleted needs of belonging and self-esteem in participants ostracised through cyberball. Videogames successfully restored affect in ostracised participants, with the pro-social game being the most effective. Videogames had no effect on pro/anti- social behavioural responses in participants. Findings offer insight into how videogames can satisfy needs and regulate mood.